1999
DOI: 10.1103/physrevlett.83.2989
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structure of theGaAs(001)(2×4)Surface Resolved Using Scanning Tunneling Microscopy and First-Principles Theory

Abstract: The atomic arrangement of the technologically important As-rich GaAs͑001͒-͑2 3 4͒ reconstructed surface is determined using bias-dependent scanning tunneling microscopy (STM) and first-principles electronic structure calculations. The STM images reveal the relative position and depth of the atomicscale features within the trenches between the top-layer As dimers, which are in agreement with the b2͑2 3 4͒ structural model. The bias-dependent simulated STM images reveal that a retraction of the topmost dangling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(91 citation statements)
references
References 29 publications
5
85
0
1
Order By: Relevance
“…Integrations in reciprocal space were performed by the Monkhorst-Pack scheme with a 12 × 12 × 12 mesh for perovskite STO, a 6 × 12 × 4 mesh for monoclinic claudetite As 2 O 3 , and a 6 × 6 × 6 mesh for cubic arsenolite As 2 O 3 , with 5, 20, and 80 atoms in the unit cell, respectively. We point out that while several previous studies on bare, As-terminated GaAs (001) surfaces have found the (2×4)-β2 surface reconstruction to be energetically favorable, [16][17][18][19] it appears that the STO deposition eliminates this surface reconstruction as inferred from our Z-contrast images.…”
Section: 8supporting
confidence: 51%
“…Integrations in reciprocal space were performed by the Monkhorst-Pack scheme with a 12 × 12 × 12 mesh for perovskite STO, a 6 × 12 × 4 mesh for monoclinic claudetite As 2 O 3 , and a 6 × 6 × 6 mesh for cubic arsenolite As 2 O 3 , with 5, 20, and 80 atoms in the unit cell, respectively. We point out that while several previous studies on bare, As-terminated GaAs (001) surfaces have found the (2×4)-β2 surface reconstruction to be energetically favorable, [16][17][18][19] it appears that the STO deposition eliminates this surface reconstruction as inferred from our Z-contrast images.…”
Section: 8supporting
confidence: 51%
“…[14][15][16] In typical MBE growth settings for homoepitaxy, the GaAs(001) substrate exhibits the As-rich β2(2×4) surface reconstruction. 15,16 Although the structure of the β2(2×4) unit cell has been well established experimentally [17][18][19][20][21][22][23][24] and theoretically, [25][26][27][28][29] Pashley and colleagues have pointed out that the twofold structural degeneracy of the β2(2 × 4) unit cell can lead to β2 (2 × 4) surfaces that have a long-range disorder associated with occupancy of out-of-phase unit cells. 24,30 Their work indicates that the disordered surface is the real template on which growth occurs and that effects associated with surface disorder may play a significant role in governing growth kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…The RHEED measurements show a c(4 and is the focus of most studies of epitaxial growth on this surface. The structure of GaAs(001)-(2 ð 4), the so-calleď 2(2 ð 4) reconstruction, has been determined by firstprinciples density functional calculations 29,52 and supported by extensive STM studies. 52 -54 A schematic representation of theˇ2(2 ð 4) reconstruction is shown in Fig.…”
Section: Phase Stabilitymentioning
confidence: 99%